1995
DOI: 10.1063/1.166104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear time series analysis of electrocardiograms

Abstract: In recent years there has been an increasing number of papers in the literature, applying the methods and techniques of Nonlinear Dynamics to the time series of electrical activity in normal electrocardiograms (ECGs) of various human subjects. Most of these studies are based primarily on correlation dimension estimates, and conclude that the dynamics of the ECG signal is deterministic and occurs on a chaotic attractor, whose dimension can distinguish between healthy and severely malfunctioning cases. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
2
18
0
3
Order By: Relevance
“…The entropy associated with the LBP subject saturates at very short-times; two orders of magnitude shorter than for the healthy subject. Furthermore, the long time entropy of LBP is lower than for the healthy subject, a result consistent with non-linear analysis of other medical time series (Bezerianos et al, 1995). It is generally observed that injuries result in a decrease in the complexity of biological systems.…”
Section: Entropy Of Electromyographysupporting
confidence: 64%
See 1 more Smart Citation
“…The entropy associated with the LBP subject saturates at very short-times; two orders of magnitude shorter than for the healthy subject. Furthermore, the long time entropy of LBP is lower than for the healthy subject, a result consistent with non-linear analysis of other medical time series (Bezerianos et al, 1995). It is generally observed that injuries result in a decrease in the complexity of biological systems.…”
Section: Entropy Of Electromyographysupporting
confidence: 64%
“…One can characterize the complexity of time series by using the information (Shannon) entropy S=-pjlogpj, where pj is the probability for outcome number 'j' of a given experiment (Allen et al, 2004;Bezerianos et al, 1995;Bezerianos et al, 2003;Costa et al, 2003). The above equation is the standard formulation of uncertainty as it has the following features: (i) the lowest entropy (S = 0) corresponds to one of the outcomes being certain [i.e.…”
Section: Entropy Of Electromyographymentioning
confidence: 99%
“…As a direct consequence of modulated redox/ROS dynamics, the aged cells up-regulate uncoupling protein homolog possibly for mitigating increased oxidative stress, which in turn contributes to diminished bioenergetics during substrate metabolism. Complex behaviors have been reported recently in various physiological signals such as heart beat intervals, gait dynamics, and respiratory signals, thus challenging the classical paradigm of homeostatic regulation (2,(7)(8)(9)(10)(11)(12)(13). Our data demonstrate for the first time that similar physiologically relevant nonlinear dynamical features are operative at the level of single cells for efficient regulation of energy metabolism.…”
mentioning
confidence: 62%
“…), влияющих на сердечный ритм и увеличивающих степень вариабельности сердечного ритма. Характер спектральных свойств шума выбран на основе известных экспериментальных результатов [2,7]. Введение шума потребовалось, так как известные модельные представления, как правило, дают заниженные значения дис-персии вариабельности сердечного ритма при физиологичных значениях прочих парамет-ров [10,14,21].…”
Section: модельunclassified